Efektivitas Pembinaan Kepribadian terhadap Anak Binaan pada Lembaga Pemasyarakatan Kelas II Maros - Rakhmat Alfian Abdillah; Sunardi Purwanda; Rafika Nur; Muhammad Darwis; Phireri Phireri (Universitas Musamus, 2026)
This study aims to analyze the implementation of personality development programs at the Class II Juvenile Correctional Institution of Maros while evaluating its effectiveness in rehabilitating the character of children in conflict with the law, ensuring their successful social reintegration without relapsing into recidivism. This empirical legal research uncovers objective field facts through structural and cultural approaches, utilizing both primary and secondary data. Data collection was scientifically conducted via direct observation and in-depth interviews, which were then analyzed descriptively and analytically using qualitative inductive reasoning. The findings indicate that while the implementation of religious programs, counseling, and character building has procedurally operated comprehensively through collaborative governance, it remains suboptimal due to the absence of a standardized national curriculum and a shortage of specifically competent correctional officers. Furthermore, the program's effectiveness has merely achieved a level of formal, pseudo-compliance. The high administrative participation rate is actually inversely proportional to the actual behavior within the housing blocks, which are still marked by indiscipline due to the strong influence of a criminal subculture among the juvenile inmates. This fundamental ineffectiveness is simultaneously driven by internal factors such as a lack of intrinsic motivation stemming from broken homes, and external factors including a monitoring gap by officers and the absence of a halfway house facility to bridge social reintegration post-release.